My little book of rocks, minerals, and gems - Martin, Claudia (QEB, 2017)
"For those with curious minds starting to take note of the world around them, the basic materials from which our planet is made raise a multitude of questions. What are rocks and minerals? Why are there so many different kinds? From the way that rocks are formed to identifying gem stones, [this book] provides the answers for budding geologists, using clear, concise text along with full color illustrations and photographs."--Amazon.com.